Culture Adventure Games: Exploring Natural Science through Local Wisdom - Jarudin; Bronto Waluyo, Edy Tekad; Sirjon (Mutiara Intelektual Indonesia Press, 2025)
The purpose of this study is to develop a natural science learning game oriented towards local Papuan culture for grade IV elementary school students that is feasible and effective. This research uses a qualitative approach with R&D (Research and Development) research methods with the Lee & Owen development model. The results of the formative evaluation showed an average feasibility test of material experts, learning design experts, and media experts of 3.94 with good conclusions, one-to-one evaluations with students obtaining an average of 3.05 with good conclusions, small group evaluations obtaining an average of 3.43 with very good conclusions, and field trial evaluations obtained an average score of 3.61 with a very good conclusion, so it was concluded that the science learning game oriented towards local Papuan culture for grade IV elementary school students was very good. Test the effectiveness of science learning game development oriented to local Papuan culture, tested through a t-test. The results show a Sig. (2-tailed) value of 0.000 < 0.05, so there is a significant difference between science learning outcomes in pretest and posttest data, and it can be concluded that science learning games oriented towards local Papuan culture are effective in improving the learning outcomes of grade IV elementary school students.